Light - Peacock, Graham (New York : Thomson Learning, 1993)
Experiments and activities introduce the scientific principles of light.
Includes bibliographical references (p. 31) and index.
Science Books & Films (A.A.A.S.).
4.5
3-6
Keywords: Light -- Juvenile literature; Light -- Experiments -- Juvenile literature; Light -- Experiments; Experiments; Light -- Experiments; Science -- Experiments; Light; Light -- Experiments; Experiments